Dissociative electron recombination of NH2CHOH+ and implications for interstellar formamide abundance. Issue 1 (21st September 2019) - Ayouz, M A; Yuen, C H; Balucani, N; Ceccarelli, C; Schneider, I F; Kokoouline, V
ABSTRACT: Formamide is a potentially important molecule in the context of pre-biotic chemistry, since reactions involving it can lead to precursors of genetic and metabolic molecules. Being abundant in cometary material and in star-forming regions, the formation and destruction routes of interstellar formamide have been the focus of several studies. In this work, we focus on the electron recombination of protonated formamide, an important step of its destruction routes, by performing rigorous ab initio calculations of this process. We found that our values are in good agreement with previous qualitative estimates of the global rate coefficients. On the contrary, we propose a substantial revision of the products and branching ratios. Finally, we justify and emphasize the importance of carrying out similar theoretical calculations on the largest possible number of complex species of astrochemical interest.